Model rodziny i wychowania rodzinnego w parafialnej prasie wielkopolskiej w II Rzeczypospolitej na przykładzie „Tygodnika Parafji Zbąszyńskiej” - Piwowarczyk, Mirosław (Karkonoska Państwowa Szkoła Wyższa, 2011)
Local press played a significant role in 2nd Polish Republic both from the perspective if state administration, territorial autonomies, political parties and the expectations of wide social environments and local communities. It fulfilled the need of information on the social, political, educational, cultural and economical life of specific environments. It also worked as a tool in propaganda and political agitation, it familiarized ideologies of political parties and expressed views and idea of local communities. It played an important part in local economy life; it educated and actively took part in popularization of interests in regional issues.Local press was both: amirror of contemporary social relations, political and national divisions and the important agent in initiatives such as cultural events. It registered and pictured life of the town and its area citizens, gave pedagogical impact on the young generation by giving them patterns and forms of positive social actions, popularized specific ideologies, educational concepts, patterns of behavior, it created and influenced the local communities attitudes and actions. Its role was especially visible in Great Poland, where local press helped in creation of socio-cultural life in small towns and education. In the group of magazines that specifically influenced local communities cultural character and had an important educational impact we should (undoubtedly) include the parish press.
Keywords: family; catholic; catholic family; education; family education; good wife-mother pattern; husband-father pattern